A systematic review on psychological and physical factors in talent identification - Hamidi, Muhammad Noor Hizami; Norjali Wazir, Mohd Rozilee Wazir (RMP Publications, 2022)
Prior studies mostly focused on physical factors such as physical fitness, motor abilities, and anthropometry as indicators for talent identification (TID). However, there are two critical issues that have been emerging recently among young athletes, which are burn-out and early drop-out. Thus, this study suggests to include another factor as an indicator for TID, which are psychological factors. The aim of this paper was to identify the psychological factors that would be good indicators for the TID programme along with the physical factors. This systematic review uses the PRISMA method to logically summarise the identified psychological and physical factors that would be good indicators for TID. A comprehensive electronic literature search was conducted via Google Scholar and open access journals. 30 literature selections were selected based on a few criteria. This systematic review conclude that a set of physical fitness, anthropometry, motor abilities and several psychological factors such as personality traits, emotional intelligence and grit should be included as TID indicators to select a physically talented athlete that have the psychological ability to endure the development process. A selected athlete might be physically competent but psychologically incompetent. This is the explanation of the importance of psychological factors must be included as indicators for the talent identification process in sports to avoid the current critical issues which are burn-out and early drop out among young talented athletes. However, a proper selection of psychological factors must be made to choose a good psychological indicator because an indicator for talent identification must be consistent throughout the time period. A longitudinal research method is required to provide more evidence for this theory